Realization of Optical Logic Gates Using the Thermal Lens Effect. Issue 2 (2002) - Kurian, Achamma; Unnikrishnan, K. P.; S., Thomas Lee; Nampoori, V. P. N.; Vallabhan, C. P. G.
Abstract : A sensitive method based on the principle of photothermal phenomena to realize optical logic gates is presented. A dual beam thermal lens method using low power cw lasers in a dye-doped polymer can be very effectively used as an alternate technique to perform the logical function such as NAND, AND and OR.